Contract management for interim certificates and payment / Azlan Abu Bakar - Abu Bakar, Azlan (2017)
Industrial training is main subject or course for Diploma in Faculty Architecture, Planning and Surveying in University Technology Mara Perak and this course is compulsory for those students pass their entire subject in last semester. For building surveying program, internship was conducted on final semester which is semester 6. If students do not pass their exam in the semester before practical, they are allowed to take a supplementary paper to justify their practical training.